"Massiliomicrobiota timonensis, " a new bacterial species isolated from the human gut. (September 2016) - Ndongo, S.; Khelaifia, S.; Fournier, P.-E.; Raoult, D.
Abstract: We report the main characteristics of a new bacterium, "Massiliomicrobiota timonensis" strain SN16 (= CSUR P2264), which was isolated from the stool of a 87-year-old patient.